Key role of surface oxidation and reduction processes in the coarsening of Pt nanoparticles. Issue 35 (29th August 2017) - Solano, Eduardo; Dendooven, Jolien; Ramachandran, Ranjith K.; Van de Kerckhove, Kevin; Dobbelaere, Thomas; Hermida-Merino, Daniel; Detavernier, Christophe
Abstract : In situ GISAXS during thermal annealing for unraveling the factors and mechanism governing the coarsening of supported Pt nanoparticles. Abstract : Particle coarsening is the main cause for thermal deactivation and lifetime reduction of supported Pt nanocatalysts. Here, Atomic Layer Deposition (ALD) was used to prepare a model system of Pt nanoparticles with high control over the metal loading and the nanoparticle size and coverage. A series of samples with distinct as-deposited size and interparticle spacing was annealed under different oxygen environments while Grazing Incidence Small Angle X-ray Scattering (GISAXS) was employed as in situ tool for monitoring the change in average nanoparticle size. The obtained results revealed three morphological stages during the thermal treatment, which can be explained by (I) the formation of a PtO2 shell on stable Pt nanoparticles at low temperature (below 300 °C), (II) the reduction of the PtO2 shell at moderate temperature (300 to 600 °C), creating mobile species that trigger particle coarsening until a steady morphological state is reached, and (III) the evaporation of PtO2 at high temperature (above 650 °C), causing particle instability and coarsening reactivation. The onset temperatures for stages (II) and (III) were found to depend on the initial particle size and spacing as well as on the O2 partial pressure during annealing, and could be summarized in a morphological stability diagram for Pt nanoparticles. The coarsening model indicates an important role for the reduction of the PtO2 shell in inducing particle coarsening. The key role of the reduction process was corroborated through isothermal experiments under decreasing O2 partial pressure and through forced reduction experiments near room temperature via H2 exposure.